A Systematic RNAi Screen Reveals a Novel Role of a Spindle Assembly Checkpoint Protein BuGZ in Synaptic Transmission in C. elegans - Han, Mei; Zou, Wenjuan; Chang, Hao; Yu, Yong; Zhang, Haining; Li, Shitian; Cheng, Hankui; Wei, Guifeng; Chen, Yan; Reinke, Valerie; Xu, Tao; Kang, Lijun (Frontiers in Molecular Neuroscience, 2017)
Synaptic vesicles (SV) store various neurotransmitters that are released at the synapse. The molecular mechanisms of biogenesis, exocytosis and endocytosis for SV, however, remain largely elusive. In this study, using Complex Object Parametric Analysis and Sorter (COPAS) to monitor the fluorescence of synapto-pHluorin (SpH), we performed a whole-genome RNAi screen in C. elegans to identify novel genetic modulators in SV cycling. 176 genes that up-regulating SpH fluorescence and 96 genes that down-regulating SpH fluorescence were identified after multi-round screen. Among these genes, B0035.1 (bugz-1) encodes ortholog of mammalian C2H2 zinc-finger protein BuGZ/ZNF207, which is a spindle assembly checkpoint protein essential for mitosis in human cells. Combining electrophysiology, imaging and behavioral assays, we reveal that depletion of BuGZ-1 results in defects in locomotion. We further demonstrate that BuGZ-1 promotes SV recycling by regulating the expression levels of endocytosis-related genes such as rab11.1. Therefore, we have identified a bunch of potential genetic modulators in SV cycling, and revealed an unexpected role of BuGZ-1 in regulating synaptic transmission.